ANALYSIS OF RECORDING AND REPORTING SYSTEM OF THE TUBERCULOSIS CONTROL PROGRAM IN PUBLIC HEALTH CENTER IN PADANG CITY - Febriani, Elvira Radhiatul (Jurnal Kesehatan Medika Saintika, 2024)
Problems in the implementation of recording and reporting of tuberculosis control programs in community health centers are still found, there are differences in the data recorded in the Tuberculosis Information System (SITB) with manual recording, which affects the quality of TB data and TB program achievement indicators. This research aims to analyze the implementation of recording and reporting of the tuberculosis program from the input, process and output aspects. This type of research is qualitative and was carried out in January-August 2023 at two health centers, namely Andalas Health Center and Pauh Health Center. Interviews were conducted with eight informants using purposive sampling technique. Recording and reporting at both health centers is carried out manually and electronically (SITB) starting from patients, laboratories and logistics. The difference found was that the recording at the Andalas Community Health Center was consistent in filling out manual and SITB forms, in contrast to the Pauh Community Health Center where there were still inconsistencies that affected the quality of the data produced. In both community health centers, incomplete data was still found. Recording is carried out every day and reporting is sent to DKK Padang in the form of monthly, quarterly and annual reports. The implementation of TB program recording and reporting at both community health centers is in accordance with implementation guidelines but is not yet optimal. It is recommended that both community health centers maximize data entry in the manual register and SITB completely.